A systemic perspective on cognition and mathematics - Forrest, Jeffrey Yi-Lin 1959- (CRC Press, 2013)
This book is devoted to the study of human thought, its systemic structure, and the historical development of mathematics both as a product of thought and as a fascinating case analysis. After demonstrating that systems research constitutes the second dimension of modern science, the monograph discusses the yoyo model, a recent ground-breaking development of systems research, which has brought forward revolutionary applications of systems research in various areas of the traditional disciplines, the first dimension of science. After the systemic structure of thought is factually revealed, math.
"A Balkema book"--Title page verso. - Includes bibliographical references and index. - Print version record
Keywords: Mathematics -- Philosophy; Cognition; System theory; Mathematics -- Psychological aspects; Mathematics -- History; Mathématiques; Philosophie; Théorie des systèmes; Mathématiques; Aspect psychologique; Mathématiques; Histoire; cognition; MATHEMATICS / History & Philosophy; MATHEMATICS; History & Philosophy; Mathematics; Mathematics; Philosophy; Mathematics; Psychological aspects; History